ATTITUDES TOWARDS WOMEN’S RIGHTS, THEIR CHARACTERISTICS (Multidisciplinary Journal of Science and Technology, 2024)
This article investigates the complex and changing attitudes toward women's rights, looking at their characteristics and influencing factors. This study analyzes historical context, cultural norms, social and economic conditions, and political frameworks to provide a comprehensive understanding of progress and ongoing challenges in achieving gender equality. Drawing on a variety of sources, the article seeks to highlight the multifaceted nature of societal attitudes toward women's rights while also providing insights into future directions for advocacy and policy development.